Low Pollinator Sharing Between Coexisting Native and Non-native Plant Pairs: The Effect of Corolla Length and Flower Abundance - Abdallah, Mohamad; Hervías-Parejo, Sandra; Traveset, Anna (Frontiers in Ecology and Evolution, 2021)
Understanding the mechanisms by which non-native plants can attract pollinators in their new geographical zones is important because such species infiltrate native communities and can disrupt native ecological interactions. Despite the large number of studies assessing how invasive plants impact plant-pollinator interactions, the specific comparison of pollination interactions between native and non-native plant pairs has received much less attention. Here we focused on four coexisting co-flowering pairs of common native and non-native species, both with abundant flowers but different floral traits, and asked: (1) to what extent native and non-native plants share pollinator species, and whether the non-native plants attract a different set of pollinators, (2) whether the most shared pollinators are the most frequent floral visitors and the most generalized in their interactions, and (3) how much of the variation in the diversity and frequency of pollinator species between native and non-native plant species can be explained by floral trait dissimilarity and flower abundance. Direct pollinator observations revealed that the plant pairs shared a low fraction (0-33%) of insect species, i.e., non-native plants tended to acquire a different set of pollinators than their native counterparts. The most shared pollinators in each plant pair were the most common but not the most generalized species, and non-native species attracted both generalized and specialized pollinators. Corolla length at opening and flower abundance showed to be important in determining the differences in flower visitation rate between natives and non-natives. Our findings support the general pattern that non-native species have no barriers at the pollination stage to integrate into native communities and that they may attract a different assemblage of pollinators relative to those that visit native plants with which they coexist.